Measurement of the Palatal Depth for Completely Edentulous Patient - Munther N Kazanje; Saad Y INoori (University of Mosul, College of Dentistry, 2008)
Aim: To measure the depth of the palate for completely edentulous patients and relate this parameter to the type of reflection of the soft palate. Materials and methods: Fixed reference point was determined in the hard palate of a hundred upper edentulous casts made by pouring impressions of completely edentulous patients attending the prosthodontic clinic in College of Dentistry, University of Mosul. This reference point was determined by drawing two lines, the first line from the center of incisive papilla to the fovea palatinae, and the second line crossing the first line exactly in its middle. The crossing point of these two lines was considered the point of measurement. A depth measuring digital vernia (Lezaco art, 2406 China) measuring to the nearest of 0.01 mm recorded the measurement. The curvature of soft palate was determined by measuring the angle formed by the highest point of the palate and a point one centimeter posterior to fovea palatinae. Results: The results showed that 65% of the measurements of the palatal depth fall in the moderate category of palatal depth and 79% of soft palate reflections were of gradual type. Conclusion: There is an acceptable success rate of complete denture could be achieved in cases of moderate palatal depth with gradual reflection of soft palate